(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program addresses the lack of structured learning approaches in skill-based activities for students with mild intellectual disabilities. The novelty of this program lies in integrating simple work standards derived from Industrial Engineering into special education practices. The program aims to improve students’ functional skills and independence through the application of simple Standard Operating Procedures (SOPs) in fruit skewer making. The activity was conducted at a Special School (SLB) involving 15 students using a participatory approach through learning by doing. The program consisted of three stages: planning, implementation, and evaluation. Data were collected using observation checklists and documentation, focusing on students’ ability to follow procedures, neatness, and independence. The results showed a substantial improvement in all indicators, particularly in the ability to follow work steps, which increased from 33% to 83%. Students also demonstrated better neatness and higher independence in completing tasks. These findings indicate that simple and visual SOPs effectively create structured learning processes that enhance students’ understanding and independence. Therefore, integrating simple work standards into special education can serve as an innovative and practical approach to improving functional skills and independence.